2017
DOI: 10.3390/rs9010066
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Urbanization Effects on Land Surface Phenology in Northeast China during 2001–2015

Abstract: Abstract:The urbanization effects on land surface phenology (LSP) have been investigated by many studies, but few studies have focused on the temporal variations of urbanization effects on LSP. In this study, we used the Moderate-resolution Imaging Spectroradiometer (MODIS) Enhanced Vegetation Index (EVI), MODIS Land Surface Temperature (LST) data and China's Land Use/Cover Datasets (CLUDs) to investigate the temporal variations of urban heat island intensity (UHII) and urbanization effects on LSP in Northeast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 55 publications
2
34
0
Order By: Relevance
“…The results showed that the urban area extracted using the method in this study was larger than that from Landsat data ( Table 2); however, it is appropriate for this study due to these reasons: (a) the footprint of SUHI was larger than the actual urban size according to previous studies [40,48,49]; (b) the urbanization primarily occurred in the suburban areas according to previous studies [26,36]; (c) the study period in this study was 2001-2016, the land cover maps used were during 2001-2013, and the urban area may expand during 2014-2016. Finally, we generated the buffer zone between 20 and 25 km from the urban areas, and we excluded the pixel with DN > 10 (SNLD) in the 20-25 km buffer and defined it as rural area [5,41]. The rural areas in this study were set larger than previous studies, since the footprint of UEs was much larger than the urban areas in previous studies [5,40,48,49].…”
Section: Extraction Of Urban Areamentioning
confidence: 92%
See 3 more Smart Citations
“…The results showed that the urban area extracted using the method in this study was larger than that from Landsat data ( Table 2); however, it is appropriate for this study due to these reasons: (a) the footprint of SUHI was larger than the actual urban size according to previous studies [40,48,49]; (b) the urbanization primarily occurred in the suburban areas according to previous studies [26,36]; (c) the study period in this study was 2001-2016, the land cover maps used were during 2001-2013, and the urban area may expand during 2014-2016. Finally, we generated the buffer zone between 20 and 25 km from the urban areas, and we excluded the pixel with DN > 10 (SNLD) in the 20-25 km buffer and defined it as rural area [5,41]. The rural areas in this study were set larger than previous studies, since the footprint of UEs was much larger than the urban areas in previous studies [5,40,48,49].…”
Section: Extraction Of Urban Areamentioning
confidence: 92%
“…The purpose was to compare the SUHII or ∆EVI in the same places across different years [5]. In addition, the urban area in the year 2001 was defined as old urban area (OUA), and the urbanized area (UA) was defined as the differences between the urban area in the year 2001 and 2013.…”
Section: Calculation Of Ues On Vegetation and Suhiimentioning
confidence: 99%
See 2 more Smart Citations
“…Time series NDVI is often used when investigating land cover or change using vegetation phenology. Methods based on line interpolation [13,14], fast Fourier transformation (FFT) [15,16], and wavelet [17][18][19] have been generally used to correct pixels containing clouds included in a time series NDVI profile. However, these correction methods have limitations in minimizing cloud effects because the input data for profile correction are also used by data affected by clouds.…”
Section: Discussionmentioning
confidence: 99%